Effect of APAO on the aging properties of waste tire rubber modified asphalt binder. (30th June 2018) - Liu, Wenyao; Yan, Kezhen; Ge, Dongdong; Chen, Ming
Highlights: Asphalt binders modified with WTR and APAO were aged in TFOT and PAV process. WTR/APAO modified asphalt has higher resistance to aging. WTR/APAO modified asphalt behaves better resistance to permanent deformation. WTR/APAO complex modification helps increase the resistance to fatigue cracking. APAO strengthened the network in WTR modified asphalt. Abstract: Amorphous poly alpha olefin (APAO) was added into the waste tire rubber (WTR) modified asphalt and its effects on aging properties of WTR modified asphalt were investigated. Thin Film Oven Test (TFOT) and Pressure aging vessel (PAV) test were conducted to simulate the short-term and long-term aging respectively. Conventional properties including penetration, softening point, and viscosity were tested; Dynamic Shear Rheometer (DSR) test were conducted both to evaluate the properties of asphalt. The results showed that higher percentage retained penetration, lower softening point increment, and smaller viscosity aging index were gained after adding APAO to WTR modified asphalt. Closer G ∗ and δ curves, smaller G ∗ ratios due to the introduction of APAO confirmed the improved aging resistance. Higher G ∗ / sin δ at high temperature and smaller G ∗ · sin δ at intermediate temperature indicates WTR and APAO are beneficial to improving resistance to permanent deformation and fatigue cracking. Fourier Transform Infrared Spectroscopy (FTIR) measurements revealed that the double bonds in APAO and WTR were consumed for building a strengthened network in WTR modified asphalt and this may explain the better anti-aging properties of WTR + APAO compound modified asphalt.